IMPLANTACIÓN DE LA CONTABILIDAD Y ANÁLISIS FINANCIERO EN LA FERRETERÍA “FERRITODO” DE LA CIUDAD DE LOJA, PERÍODO DEL 01 DE ENERO AL 30 DE ABRIL DEL 2014 - Cueva Pardo, Carmen Liliana (2015)
This thesis entitled "IMPLEMENTATION OF ACCOUNTING AND FINANCIAL ANALYSIS IN THE HARDWARE" FERRITODO "CITY OF LOJA, PERIOD 01 JANUARY TO 30 APRIL 2014", he focused on meeting the specific objectives where a plan and a manual of accounts according to the economic movement of the company was drawn up, structuring the plan from sorting, coding and name of accounts that conform with their respective description in the operating accounts. Then the accounting process, starting from the Initial Inventory, State Initial Situation, Daybook, Ledger, Trial Balance, Worksheet with their respective adjustments up to determine the financial statements, in order to know the economic situation developed and financial company. Finally indicators of liquidity, activity, indebtedness, profitability and financial analysis was applied which helped assess the economic and operational performance of the company and in particular to facilitate the proper decision-making by the owner. As for the methodology used materials and methods they were applied and helped to develop theoretical and practical knowledge becoming the key part to fulfill the objectives are presented. 5 Regarding the completion of this thesis according to the results of the respective conclusions and recommendations on the most important aspects of it is presented. Upon completion of this investigative work you could verify the correct implementation of accounting and financial analysis allowed to know the economic and financial situation in a timely and reliable manner, demonstrating to consider this proposal for a thesis for the hardware can process efficiently accounting information contributing to sustained growth necessary to meet and exceed the business needs for making better decisions.